2021
DOI: 10.1002/anie.202110658
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry‐Guided Prediction of the Absolute Configuration of Fungal Reduced Polyketides

Abstract: Highly reducing polyketide synthases (HR-PKSs) produce structurally diverse polyketides (PKs). The PK diversity is constructed by av ariety of factors,i ncluding the b-keto processing,c hain length, methylation pattern, and relative and absolute configurations of the substituents.W e examined the stereochemical course of the PK processing for the synthesis of polyhydroxyPKs such as phialotides,phomenoic acid, and ACR-toxin. Heterologous expression of aH R-PKS gene,atrans-acting enoylreductase gene,and atruncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…The OpdC served as trans -acting ER and reduced the terminal alkenyl to alkane. According to the stereochemical rule proposed by Oikawa and coworkers [ 16 ], the absolute configurations in C15 and C17 were formed at the chain extension stages in the PKS-NRPS assembly line ( Figure S31 ). The differences between 15 S , 17 R in 1 and 15 R , 17 S in 2 were generated by non-stereospecific catalysis of the ketoreductase (KR) domain and enoyl reductases.…”
Section: Resultsmentioning
confidence: 94%
“…The OpdC served as trans -acting ER and reduced the terminal alkenyl to alkane. According to the stereochemical rule proposed by Oikawa and coworkers [ 16 ], the absolute configurations in C15 and C17 were formed at the chain extension stages in the PKS-NRPS assembly line ( Figure S31 ). The differences between 15 S , 17 R in 1 and 15 R , 17 S in 2 were generated by non-stereospecific catalysis of the ketoreductase (KR) domain and enoyl reductases.…”
Section: Resultsmentioning
confidence: 94%
“…For the stereochemistry of reported mono-/bis-alkenoic acid derivatives, the configurations of C-7 (7′) and C-13 (13′) were conserved to be 7 R (7′ R ) and 13 S (13′ S ) ( Liu et al, 2018 ; Niu et al, 2019 ; Tang et al, 2019 ), while the configuration of C-12 (12′) turned out to be 12 (12′) R or 12 (12′) S ( Liu et al, 2018 ). Recently, it was reported that the configurations of fungal polyketides were conserved in general with few exceptions ( Takino et al, 2021 ). Therefore, in view of the shared biosynthetic pathway of mono-/bis-alkenoic acid derivatives, as well as previous literature reports ( Liu et al, 2018 ; Niu et al, 2019 ; Tang et al, 2019 ), the configurations of C-7 (7′) and C-13 (13′) in 2 were supposed to be 7 R (7′ R ) and 13 S (13′ S ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of multiple PKS intermediates by one KR domain is reminiscent of HR-PKS, for which a common stereochemical explanation for substrate-dependent stereoselectivity was recently devised. 31 MycKRB is a general B-type KR that acts as B0-or B1-type depending on the biosynthetic precursor. 19,27 The KR domains were produced as N-terminal His 6 -tagged fusion proteins by heterologous expression in Escherichia coli and purified (Figure S1).…”
mentioning
confidence: 99%
“…Detailed studies with a larger number of KRs and substrate surrogates that cover a broader structural range are clearly necessary as well as the linking of in vitro results to KR and PKS module structural data. Particularly the outcome of KR reactions with polyketides of backbone lengths > C 6 could provide new insights, as such have only been applied in a few in vitro studies with KR domains from HR-PKS 30,31 and multimodular type I PKS. 27,35 It will also be important to reassess the observed performance of KR domains in the whole PKS module environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation